A NOTE ON THE FATE OF TARTRATES IN THE BODY - Underhill, Frank P. (The Rockefeller University Press, 1913)
Under the experimental conditions outlined, sodium tartrate subcutaneously introduced into rabbits fails to reappear in the urine. It is concluded that the disintegrative influence of the salt upon the convoluted tubules is sufficient to account for the failure of the salt to be eliminated. No evidence of a vicarious function on the part of the glomerulus was observed.